Genotype × Environment Interaction and Stability of Field Pea (Pisum sativum L.) Genotypes for Seed Yield in Northwestern Ethiopia - Zeleke, Bantalem; Esimeal, Jemale; Amogne, Kindu; Mengie, Yitayal; Sendekie, Fentansh; Hailu, Abebe; Taye, Yasin (Department of Agronomy and Horticulture, IPB University, 2024)
Field pea (Pisum sativum L.) is a self-pollinated diploid (2n=14) annual cool-season pulse crop. It is a major food legume with a valuable and cheap source of plant protein having essential amino acids that have high nutritional value for resource poorhouseholds. Biotic stress such as weed and insect pests and abiotic stresses like water logging, soil acidity, and low soil fertility are the major constraints to field pea production and productivity. Fourteen field pea genotypes, obtained from Holeta Agricultural Research Center, were evaluated in eight environments in Northwestern Ethiopia in the main production season (2018-2019) to identify stable and high-yielding field pea genotypes. The trial was laid out using a randomized complete block design and replicated three times. Combined analysis of variance for seed yield revealed that genotype, environments, and genotype-by-environment interaction effects were significant (P < 0.05). The lowest hundred seed weight value (12.83 g) was manifested by the local check, while the highest value (20.73 g) was revealed by EH 07007-3 genotype from the overall mean of location. The highest mean grain yield of 2400 kg.ha-1 was obtained from the EH08003-2 genotype, while the lowest yield 1660 kg.ha-1 was obtained from EH 08041-3. The maximum grain yield of 4140 kg.ha-1 was recorded from Debark by EH 09015-3 genotype, while the minimum grain yield of 560 kg.ha-1 was revealed by EH 08041-3. The environments, GxE, and genotypes accounted for 74.8%, 16.3%, and 7.0% of the total sum squares, respectively, indicating that field pea seed yield was significantly affected by the changes in the environment, followed by GxE interaction and genotypic effect. The candidate genotype, EH08003-2, was the most stable genotype followed by EH 09068-2 and EH 08042-2 having an IPCA score closer to zero with a yield advantage of 26.3% and 36.4% over the standard and local checks, respectively. Considering the eight environments’ data and field performance evaluation during the variety verification trial, the National Variety Releasing Committee has approved the official release of EH08003-2 for kik seed utilization class with a vernacular name of Hasset for high potential areas of Northwestern Ethiopia and similar agro-ecologies.